Сопоставительный анализ глаголов с семантикой чрезмерной интенсивности действия в русском и польском языках - Dzienisiewicz, Daniel (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is an attempt to present the characteristics of Russian and Polish verbs with the meaning of the excessive intensity of action in a possibly concise form. The analyzed lexical units have been retrieved from Russian and Polish dictionaries on the basis of the existing source literature and the author’s own investigations. The aim of the article is to compare the word formative structure of the verbs and analyze their semantics on the basis of the prefixes occurring in the lexical material. The quantitative and qualitative analyses have been conducted. The cases of word-formative synonymy have been described and the largest groups of lexical synonyms have been highlighted.